Characteristics and global occurrence of human pathogens harboring antimicrobial resistance in food crops: A scoping review - Brunn, A.; Kadri-Alabi, Z.; Moodley, Arshnee; Guardabassi, L.; Taylor, P.; Mateus, A.; Waage, Jeff (Frontiers Media, 2022)
Background: The role of the crop environment as a conduit for antimicrobial resistance (AMR) through soil, water, and plants has received less attention than other sectors. Food crops may provide a link between the agro-environmental reservoir of AMR and acquisition by humans, adding to existing food safety hazards associated with microbial contamination of food crops.